Application of Dissolved Air Flotation in Metal Plating Wastewater Treatment: A Life Cycle Perspective - Ozturk, Dilsad Elif; Canci, Baris; Manav-Demir, Neslihan (HARD, 2026)
The metal plating industry is among the most rapidly developing and widely used industrial processes worldwide, consuming large amounts of water and generating significant environmental problems due to its wastewater. In this study, real wastewater from the metal plating industry was treated, and heavy metals were removed using a pilot-scale treatment process with a total volume of approximately 2.2 m3. The process consisted of sequential coagulation, flocculation, and dissolved air flotation (DAF), which was employed to reduce the area required for sedimentation. Initially, laboratory-scale studies were conducted to optimize the mixing speed, as well as the coagulant/flocculant type and dosage. Pilot-scale studies were then conducted. The study yielded removal efficiencies for COD, Cu, Ni, Zn, CN-, Cr+6, and SO42- in the coagulation/flocculation/DAF (CF-DAF) process of 83%, 33%, 94%, 99%, 46%, 99%, and 90%, respectively. Additionally, a life cycle assessment was performed using two different methods (ReCiPe 2016 Midpoint (H) and Environmental Footprint 3.1 (EF 3.1)). Environmental impact categories of the process, such as climate change, eutrophication, human toxicity, and resource depletion, were determined, and the factors that provided the highest contribution were identified.
Keywords: metal plating wastewater; dissolved air flotation; life cycle assessment (LCA); wastewater treatment; heavy metal removal; REMOVAL; WASTEWATERS; SLUDGE; COPPER; REUSE; Environmental Sciences & Ecology